The Dimensions of Space in the Narrative Works of Abdul Haleem Mahudour: (The Plain and Exceptional Shadow) as a Model - Sami Hashim, Researcher.Zahraa; Jawad Habib Al-Badrany, Prof. Dr. Mohammed (Basra studies journal, 2024)
Space has a presence in creative/narrative texts as it embodies a complementary role in arranging events, besides its mutual influence between the narrative character and the setting. The latter carries symbolic and mythical connotations that entail an interpretative vision for the reader. This, in turn, falls within other contexts that work to form a cohesive fabric of the employed settings in the narrative work. Accordingly, the research aims to study the spatial dimensions in the narratives of Abdul Haleem Mahudour, which carry different ideologies operating in an imaginative space, continuous permanence, and temporal anticipation constructed by the writer in his narrative. Therefore, the research saw the need to focus on the geographical, psychological, and historical dimensions, essential material for study due to their symbolic and aesthetic impact in the context of the text, as these dimensions interact with the confined space of the setting, which reveals the nature of the narrative elements.